Longitudinal study on work related and individual risk factors affecting radiating neck pain. Issue 5 (1st May 2001) - Viikari-Juntura, E; Martikainen, R; Luukkonen, R; Mutanen, P; Takala, E-P; Riihimäki, H
Abstract : OBJECTIVES: To study the effects of work related and individual factors affecting radiating neck pain. METHODS: A longitudinal study was carried out with repeated measurements. A total of 5180 Finnish forest industry workers replied to a questionnaire survey in 1992 (response rate 75%). Response rates to follow up questionnaires in 1993, 1994, and 1995 were 83%, 77%, and 90%, respectively. The outcome variable was the number of days with radiating neck pain during the preceding 12 months with three levels (<8, 8–30, >30 days). The generalised estimating equations method was used to fit a marginal model and a transition model was used in a predictive analysis. RESULTS: Items showing associations with radiating neck pain in both analyses were sex, age, body mass index, smoking, duration of work with a hand above shoulder level, mental stress, and other musculoskeletal pains. In the transition model, radiating neck pain in a previous questionnaire was included in the model. Although it was a strong predictor, the variables already mentioned retained their significance. CONCLUSION: Programmes targeted to reduce physical load at work, mental stress, being overweight, and smoking could potentially prevent radiating neck pain.